`Love of Wealth' and Economic Growth - Günther Rehme (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper complements research on how love of wealth bears on key variables in a Ramsey-Cass-Koopmans growth framework. It is shown that for an optimum the social planner cannot have an excessive love of wealth. If the planner has the `right' love of wealth an optimum exists and implies higher long-run per capita capital, income and consumption relative to the standard optimal growth model. The optimum implies dynamic efficiency with the possibility to get arbitrarily close to the Golden Rule where long-run per capita consumption is maximal. It is shown that the optimal path is attaining its steady state more slowly. Thus, the beneficial effects of love of wealth materialize later than in the standard model. Furthermore, the economy can be decentralized as a competitive private ownership economy. One can then identify love of wealth with the ``spirit of capitalism''. The paper, hence, implies that one needs a 'right' level of the ``spirit of capitalism'' to realize any beneficial effects for the long run.
Keywords: O40; P40; A10; 330